PEMBERDAYAAN PEREMPUAN MELALUI KESENIAN GEJOG LESUNG PADA KOMUNITAS SANGGAR SANGIR DI KABUPATEN SRAGEN - Indriani, Novita; Kiswanto, Kiswanto; Utami, Fawarti Gendra Nata (Institut Seni Indoensia Surakarta, 2023)
Gejog Lesung is folk traditional music that still survives and develops in various rural agricultural areas in Java. The research aims to look at the relationship or connection between the existence of women, gejog dimples, and the Sanggar Sangir group in Sragen, as well as the role and contribution of the three in maintaining traditions passed down from ancestors for more diverse development purposes. This research uses a qualitative approach, which is carried out through data collection stages, including observation, interviews and literature study, as well as data analysis stages through descriptive and analytical interpretation methods to end with drawing conclusions. The results of this research show that the art of gejog mortar in the Sanggar Sangir group has (1) become a forum for expression and self-actualization for women to appear in public; (2) provided a forum for women, especially mothers, and teenagers, to interact with each other and exchange information that is useful in maintaining close social relations; and (3) become a means of empowering women in their participation to increase progress in the economic, social and cultural fields.